Mechanoresponsive stem cells acquire neural crest fate in jaw regeneration. (22nd November 2018) - Ransom, Ryan; Carter, Ava; Salhotra, Ankit; Leavitt, Tripp; Marecic, Owen; Murphy, Matthew; Lopez, Michael; Wei, Yuning; Marshall, Clement; Shen, Ethan; Jones, Ruth; Sharir, Amnon; et al.
Abstract During both embryonic development and adult tissue regeneration, changes in chromatin structure driven by master transcription factors lead to stimulus-responsive transcriptional programs. A thorough understanding of how stem cells in the skeleton interpret mechanical stimuli and enact regeneration would shed light on how forces are transduced to the nucleus in regenerative processes. Here we develop a genetically dissectible mouse model of mandibular distraction osteogenesis—which is a process that is used in humans to correct an undersized lower jaw that involves surgically separating the jaw bone, which elicits new bone growth in the gap. We use this model to show that regions of newly formed bone are clonally derived from stem cells that reside in the skeleton. Using chromatin and transcriptional profiling, we show that these stem-cell populations gain activity within the focal adhesion kinase (FAK) signalling pathway, and that inhibiting FAK abolishes new bone formation. Mechanotransduction via FAK in skeletal stem cells during distraction activates a gene-regulatory program and retrotransposons that are normally active in primitive neural crest cells, from which skeletal stem cells arise during development. This reversion to a developmental state underlies the robust tissue growth that facilitates stem-cell-based regeneration of adult skeletal tissue. Reversion of adult skeletal stem cells to a developmental state underlies the growth of new bone during jaw regeneration, in a process that relies on mechanotransduction via the focal adhesion kinase protein.